The story of Ferdinand - Leaf, Munro 1905-; Lawson, Robert 1892-1957. (New York Viking Press, 1936)
Ferdinand likes to sit quietly and smell the flowers, but one day he gets stung by a bee and his snorting and stomping convince everyone that he is the fiercest of bulls.
Keywords: Bulls -- Fiction